1986
DOI: 10.1097/00000658-198604000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 and Survival in Patients with the Adult Respiratory Distress Syndrome

Abstract: A 7-day infusion of prostaglandin E1 (PGE1), an immunomodulator, was evaluated in a prospective, randomized, placebo-controlled, double-blinded trial in surgical patients with the adult respiratory distress syndrome (ARDS). The drug seemed to improve pulmonary function--only two PGE1 patients died with severe pulmonary failure compared with nine placebo patients (p = 0.01). Survival at 30 days after the end of the infusion--the predetermined end point of the study--was significantly better in the patients give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…It has provements in gas exchange and survival, a been shown to inhibit chemotaxis and the activation randomized, double-blinded, multicenter trial of of neutrophils in animal models of sepsis and ALI/ patients with ARDS showed no survival advantage. 85,86 ARDS, the release of tumor necrosis factor by macroAs a result of that study, PGE 1 fell out of favor until phages in response to endotoxin, and platelet aga recent randomized, double-blinded trial that used gregation in response to inflammatory stimuli. 76 liposomal encapsulated PGE 1 in 177 patients with Several animal models of lung injury have dem-ARDS.…”
Section: Anti-adhesion Molecule Therapy Antiendotoxin and Anticytokinmentioning
confidence: 99%
“…It has provements in gas exchange and survival, a been shown to inhibit chemotaxis and the activation randomized, double-blinded, multicenter trial of of neutrophils in animal models of sepsis and ALI/ patients with ARDS showed no survival advantage. 85,86 ARDS, the release of tumor necrosis factor by macroAs a result of that study, PGE 1 fell out of favor until phages in response to endotoxin, and platelet aga recent randomized, double-blinded trial that used gregation in response to inflammatory stimuli. 76 liposomal encapsulated PGE 1 in 177 patients with Several animal models of lung injury have dem-ARDS.…”
Section: Anti-adhesion Molecule Therapy Antiendotoxin and Anticytokinmentioning
confidence: 99%
“…The combined anti-inflammatory and anti-aggregatory activity suggested that PGE, might also be useful for the treatment of ARDS, which is often seen in association with major trauma, surgery of sepsis. Although the pathogenesis of ARDS remains unknown, the syndrome seems to be related to pulmonary damage by inflammation and coagulation [33,78]. In a prospective, randomized, placebo-controlled, double-blind pilot trial, the survival 30 days after the end of infusion was significantly better in patients given PGEl (71 %) than in the placebo group (35%) [78], indicating a potential therapeutic efficacy of PGEl in this syndrome.…”
Section: Effects On Polymorphonucleur Neutrophilsmentioning
confidence: 99%
“…A number of investigators have studied the effects of systemic vasodilators (e.g., sodium nitroprusside, diltiazem, ketanserin, prostaglandin E 1 , and nitroglycerin) in patients with ARDS/ALI (86)(87)(88)(89)(90)(91)(92). While all these medications caused pulmonary vasodilation, all also increased intrapulmonary shunting indicating that at least some of the pulmonary hypertension in ARDS is the result of increased vascular tone, presumably in response to alveolar and/or mixed venous hypoxia.…”
Section: Effects Of Vascular Tonementioning
confidence: 99%